Biotechnologies for inclusive development: Scaling up, knowledge intensity and empowerment (the case of the probiotic yoghurt ‘yogurito’ in argentina) - Bortz, Gabriela Mijal (2017)
This paper analyses how technological and institutional innovation strategies were deployed towards achieving a high-scale, sustainable, knowledge intensive, locally grounded project, through the experience of an Argentinean biotechnology-based nutritional supplement delivered in schools to solve child malnutrition led diseases. The paper focuses on how the case of ‘Yogurito’ managed to address three challenges within recent Innovation for Inclusive Development literature: (1) involving heterogeneous actors in the innovation process within knowledge intensive technologies, (2) gaining scale while fostering participatory technology development processes, and (3) promoting the articulation of science, technology and innovation (STI) programmes with wider (social, sanitary and productive) policies. Through the trajectory of the probiotic yoghurt, the article examines learning and innovation strategies in technological design and institutional arrangements. We argue that the organizational strategies deployed to articulate scientific and locally grounded capacities were key elements that allowed the programme’s working, its sustainability over time, and the unfolding of a regional development policy scheme.